(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2017)
Santo Tomás University in Tunja, has as one of its main objectives, the training of high quality professionals. For this reason, it has carried out the creation of new educational spaces, contemplated through the construction of a building called the Santo Domingo Building, which until now is under construction. The analysis of environmental damage was developed through different methodologies taking into account that today buildings are causing significant impacts on the planet, impacts that can be determined and qualified according to time through various evaluative processes in order to achieve environmental and economic sustainability for new buildings. Through this article we will present several ways that were carried out to determine the environmental impact that the Santo Domingo building would cause in three stages as they are; the adequacy of the land, construction and maintenance, in such a way that this assessment was carried out through matrices that allowed us to calculate the magnitude and importance generated by a construction in the environment in order to propose the mitigation processes, generating possible solutions to the most relevant impacts.